Determination of salt dynamics in leached water from cultivated onions (Allium cepa) under two irrigation systems in the Samacá-Boyacá Valley - Cely-Reyes, Germán Eduardo; Fernández-Pérez, Carlos Julio; Walteros-Torres, Ingrid Yaneth; Camargo-Guerrero, Fabiola del Rosario; Serrano-Cely, Pablo Antonio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The water used for agricultural irrigation has significant effects on crop production, along with chemical degradation of soil and water. This study determined the salt dynamics in two irrigation systems for bulb onion cultivation in the Samacá Valley, Colombia. Water samples were taken from the irrigation (reservoir) and the crop with lysimeters. The pH, sodium, potassium, calcium, magnesium, sulfates, chlorides, electrical conductivity (EC), and sodium adsorption ratio (RAS) index were measured. The T-student test was applied to independent samples for the response variables. Significant differences were found between the irrigation systems for EC and SO4 at 100 dat. The irrigation water (reservoir) was classified as C3-S1. The leached water in the two irrigation systems, according to the relative concentration of Na+ with respect to Ca+2 and Mg+2 (RAS) and CE, was C4-S1. Therefore, the water had a high probability of salinization, not suitable for irrigation, meaning that management plans must be carried out to prevent soil and water degradation. These results can be used to develop a sustainable management plan for water and soil resources in the Samacá Valley to prevent loss of productive land.